The effectiveness of platelet rich plasma therapy in chronic sinusitis patients with odor disorder undergoing endoscopic sinus surgery - Gökçe Kütük, Sinem; Topuz, Muhammet Fatih; Güvey, Ali; Açıkgöz, Çağrı (The European Research Journal, 2022)
Objectives: In this study, the objective was to compare the effectiveness of fluticasone dipropionate and platelet-rich plasma treatments added to the treatment in patients undergoing functional endoscopic sinus surgery in patients with chronic sinusitis involving odor dysfunction, different stages and types of sinusitis. Methods: The study included a total of 60 patients between 18 and 60 years who underwent endoscopic sinus surgery due to chronic paranasal sinus infection followed by olfactory dysfunction. Group 1: paranasal sinus surgery + steroid therapy (first 30 patients) and Group 2: paranasal sinus surgery + steroid therapy + PRP therapy (second 30 patients) were grouped together without the patients’ knowledge of the operating physician and of the treatment protocol. For the paranasal sinus CT evaluation, Lund-Mackey staging was used and the degree of the disease was determined using the Kennedy staging system. Modified Sniffin Stick test was applied to all patients in the preoperative 1st week and in the 3rd month postoperatively. The Modified Sniffin Stick test was conducted on all patients during the preoperative 1st week and the postoperative 3rd month. The modified Sniffin Stick test and endoscopic evaluation score were evaluated and whether or not the patients benefited from PRP treatment were compared. Results: According to the postoperative endoscopy score, there was a difference between the experimental group and the control group in terms of postoperative endoscopy score, and it was found to be statistically significant. Besides, the postoperative endoscopy score of the experimental group was found to be lower than the control group. The average of Modified Sniffin’ Stick Test scores in the postoperative period of the patients in the study was 28.27 ± 7.88 for the experimental group, while it was determined as 20.08 ± 5.75 for the control group, and this difference was statistically significant. The average anosmia times of the experimental and control group patients in the study were compared, and the mean duration of anosmia was 48.53 ± 20.40 (6-96) for the experimental group and 44.27 ± 19.45 (6.96) for the control group. The difference in the mean duration of anosmia between the experimental and control groups was not found statistically significant. Conclusions: In this research, PRP, which is applied to functional endoscopic sinus surgery and fluticasone dipropionate treatment, has been shown to be a readily applicable, safe and highly efficient method of treatment in patients with chronic sinusitis accompanied by smell dysfunction.